Sugar Coating Grammar Lessons: The Effective Use of a Dramatic Approach in Teaching Reported Speech to Undergraduates of a State University in Sri Lanka - Jayasinghe, J.A.K.M.; Vithanage, R.I. (University of Jaffna, 2025)
Grammar instruction in learning and teaching English encompasses many challenges and is perceived by students to be a burden. The already existing resistance towards the language learning process intensifies when grammar instruction takes place in class. However, in undergraduate courses which focus on English for Academic Purposes (EAP), helping students master grammar structures in order to better produce and perform in language related contexts is compulsory. Therefore, sugar coating grammar lessons could be considered one of the best methods to use in order to refrain from building resistance towards the language learning process. Hence, this study aims to help students master Reported Speech by creating an enabling space using texts/examples which are not necessarily academic, but which provide interesting and entertaining real-life scenarios, and thereby attempt to remove the sense of overburden, anxiousness prevalent in understanding grammar. This study presented EAP students of a state university with a grammar lesson designed in the following steps: 1) Ice-breaker: the introduction to Reported Speech; practiced with real life scenarios 2) Engaging activities to practice usage: role-play, script writing, summarizing dialogues, 3) Concluding activities: peer review and feedback. The key feature of these activities is that they are designed based on a dramatic approach, specifically focusing on Sri Lankan plays and movies, embedded with a variety of local flavours. These activities are also used as scaffolding to help students generate their own ideas and practice the actual language usage on their own. The study also incorporates existing scholarly literature on lesson material preparation and development by scholars such as Arjuna Parakrama and Suresh Canagarajah. By acknowledging their contribution to the discourse on ELT, this study promotes the importance of the usage of context-sensitive material which is linguistically as well as culturally relevant, referring to local knowledge and lived experience. The findings of the study indicated that the students enjoyed the process of learning the Reported Speech. Their feedback suggests that they learnt the grammar not knowing that they learnt it. In other words, the activity-based approach helped sugar coat an otherwise daunting task of learning the grammar structure/ formation, and usage. Therefore, it can be concluded that presenting grammar lessons as activity based lessons decreases resistance to learning them.
Keywords: Reported speech; Grammar; Dramatic approach; EAP